2019
DOI: 10.1101/838003
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Stress-induced myonectin improves glucose homeostasis by inhibiting glycemic response to HPA axis

Abstract: One Sentence Summary: Chronic stress breaks glucose intolerance cycle to resist diet-induced obesity, through myonectin-mediated inhibition of glycemic response to epinephrine (EPI) and activation of insulin signaling in adipose tissues. GraphicalAbstract Stress AAV+ Sympathetic output HFD 2wk Glucose intolerance 4wk Insulin sensitivity ↓ EPI sensitivity ↑ 3wk Glucose intolerance↑ Insulin sensitivity↑ Insulin sensitivity↑↑ P-Akt Ser473↑ EPI sensitivity↑ Thermogenesis↑ Insulin sensitivity↑ P-Akt Ser473↑ EPI sen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 58 publications
(43 reference statements)
0
1
0
Order By: Relevance
“…This situation can be considered as valid for GDM, whose pathophysiology is comparable to T2DM. It is well-documented that exercise and stress training have favorable effects on glucose homeostasis through myonectin expression [ 24 ] . A study that assessed serum myonectin levels in T2DM and obese patients revealed that the myo nectin level was lower among T2DM and obese patients [ 13 ] .…”
Section: Gdmmentioning
confidence: 99%
“…This situation can be considered as valid for GDM, whose pathophysiology is comparable to T2DM. It is well-documented that exercise and stress training have favorable effects on glucose homeostasis through myonectin expression [ 24 ] . A study that assessed serum myonectin levels in T2DM and obese patients revealed that the myo nectin level was lower among T2DM and obese patients [ 13 ] .…”
Section: Gdmmentioning
confidence: 99%